Students' Identities and Pedagogical Challenges - Maureen Camacho-Oviedo; Rocío Castillo-Cedeño; Heidy León-Arce; Alfredo Miranda-Calderón; Zulay Pereira-Pérez; Erika Vásquez-Salazar (Universidad Nacional, Costa Rica, 2013)
This article is a result from the orientation process carried out for the first-year students of four study programs of the Basic Education Division at the Center for Research and Teaching in Education (CIDE), Universidad Nacional, Costa Rica, in 2012. Information from 110 students was collected and analyzed with the purpose to identify the students' identity traits and possible pedagogical challenges associated. The actions taken during the design and execution of the orientation process and the data collected through different instruments were taken into account for the analysis. The findings include strong areas, as well as areas "to be developed" which represent the pedagogical challenges of the academic unit. The Basic Education Division (or School of Basic Education) plays a fundamental role in the country's social and cultural transformation preparing professionals in Education and providing students with the necessary tools for developing better skills in areas such as art, writing, technology, sports, and public speaking. These are some of the challenges emerging from the analysis of the orientation process for first-year students.